PENGARUH PENGGUNAAN KAPUR PADAM SEBAGAI BAHAN PENGISI (FILLER) PADA KETAHANAN PENGELUPASAN BETON ASPAL LAPIS AUS (AC-WC) - Mashuri, Mashuri; Batti, Joy Fredi; Listiana, Listiana (MEKTEK, 2013)
Asphalt Concrete Wearing Course (AC-WC) Pavement is located at the upper layer indirect contact with the vehicle wheel, rain and sunshine. This condition causes the pavement layer AC-WC susceptible to damagecaused by traffic loads, the influence of water and the hot sun as stripping. Currently, much effort has beendone such as the use of hydrates lime as an additive to improve the durability of the AC-WC pavement from damage. However, this study tries to use hydrates lime as a filler material in view of its influence onstripping resistance of AC-WC pavement. The purpose of this study was to determine the effect of the use of hydrates lime as a filler material to stripping resistance of AC-WC pavement. The test have been done on each percentage of hydrat lime: 0%, 25%, and 50%. Testing of AC-WC pavementto stripping resistance using Immersion Compression Test to obtain the Index of Residual Strength (IRS)AC-WC pavement. Value of the residual strength index is an indicator of stripping resistanceof asphalt pavement. Testing of Immersion Compression Test using a Universal Testing Machine (UTM) atthe test temperature is 250C. Testing of Immersion Compression Test conducted for each percentage ofhydrate lime on the condition of Optimum Asphalt Content. The results of the study found that the use ofhydrat lime as a filler material can affect the stripping resistance of AC-WC pavement. This is indicated bythe increased value of the IRS pavement using hydrates lime as a filler material than without the use ofhydrate lime. The study also found that the IRS maximum value is 96.03% in the hydrat lime content of 25% and aminimum value of 94.48% IRS on the hydrate lime content of 50%.Keywords: Stripping resistance, hydrate lime, IRS